2000
DOI: 10.1021/bk-2000-0758.ch015
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Citrus Limonoids in Insect Pest Management

Abstract: Limonin and other citrus limonoids act as insect repellents, feeding deterrents, growth disrupters, and reproduction inhibitors against several pest species across a wide range of agricultural crops. We have investigated how these allelochemic properties can be deployed as ecologically sound methods of insect pest management and reduce dependence on conventional, synthetic insecticides in potato production. In a multi-stage process of study and product development, we demonstrated that field populations of Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The main biological activity associated to these compounds is their insect antifeedant property [ 32 , 33 ]; furthermore, their antitumoral activities have been reported from in vitro and in vivo studies [ 34 ]. These natural products are also readily available from waste products (seeds, peel, molasses, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…The main biological activity associated to these compounds is their insect antifeedant property [ 32 , 33 ]; furthermore, their antitumoral activities have been reported from in vitro and in vivo studies [ 34 ]. These natural products are also readily available from waste products (seeds, peel, molasses, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…In citrus, limonoids consist of 37 limonoid aglycones and 17 limonoid glucosides ( Alford and Murray, 2000 ; Chowdhury et al, 2003 ; Patil et al, 2009 ). Previous research reported that TFs could regulate multiple genes in the biosynthesis of indole alkaloids ( Van Moerkercke et al, 2015 ), artemisinins ( Yu et al, 2012 ; Zhang et al, 2015 ), anthocyanins ( Butelli et al, 2012 ; Rinaldo et al, 2015 ) and flavonols ( Misra et al, 2010 ; Stracke et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limonoids are one of the most important classes of phytochemicals predominantly produced in the Rutaceae, Meliaceae, Cneoraceae, and Simaroubaceae families, with citrus being the only one among them that produce edible fruits. Evaluation of the biological activity of citrus limonoids has revealed the potential of these compounds in anticancer, antimicrobial, antioxidant and insecticidal capacities ( Alford and Murray, 2000 ; Chowdhury et al, 2003 ; Ono et al, 2011 ; Kim et al, 2013 ). Limonoids exist in a number of plant organs and tissues such as stems, leaves, seeds and fruit tissues ( McIntosh et al, 1982 ; Rouseff and Nagy, 1982 ; Herman et al, 1989 ; Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Progeny deterrent, antifeedant, egg hatching inhibition activity was documented after application of 5-10 μl citronellol against Callosobruchus analis [78]. Compounds like limonoids act as synergists to enhance the activities of other biological and or synthetic insecticides [79]. We recorded medium larvicidal and adulticidal potential of limonene against Aedes aegypti, but found higher toxicity when combined with diallydisulphide and carvone respectively [80].…”
Section: Citrus Eo Compounds Against Insect Spmentioning
confidence: 97%